The Decline of the Shepherd Metaphor as Royal Self-Expression1. Issue 1 (2nd January 2019) - Varhaug, Jørn
ABSTRACT: In the Old Testament, shepherd is a common metaphor of kingship, and this metaphor is sometimes also used to denote the Israelite god as a ruler (See for instance HALOT entry הער ). In Assyrian, Babylonian, Egyptian and Greek works this metaphor is remarkably more common in pre-exilic literature than in the later Greek and Roman literature, where it is almost absent. In this article I argue that shepherding was central to Assyrian and Babylonian ruling class identity, while absent as royal self-expression in the Persian, Achaemenid Empire. The imageries of these empires were influential as models for court life throughout the Ancient Near East, and beyond.